Impact of Omicron BA.5 infection on maternal and neonatal outcomes - Lu Li; Lu Li; Ruitian Hou; Ruitian Hou; Zan Mai; Li Liang; Zheng Li; Bin Long; Lin Chen; Ping Feng; Baojun Yang; Lijie Yang; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionPhysiological and immunological adaptations during pregnancy may elevate the risk of adverse perinatal and neonatal outcomes associated with SARS-CoV-2 infection. This retrospective study aimed to explore the clinical characteristics of pregnant women and the maternal and neonatal outcomes during pregnancy following Omicron BA.5 variant infection.MethodsClinical and laboratory data from 208 pregnant women with Omicron BA.5 infection were analyzed, including intrapartum and postpartum records of 24 infected parturients and their neonates, with comparisons made to uninfected controls. Multiple specimen types, including placental membranes and amniotic fluid, were collected for SARS-CoV-2 RNA detection.ResultsAmong 208 infected pregnant women, 91.8% (191/208) had received at least one dose of inactivated SARS-CoV-2 vaccine. BA.5 infection in pregnant women exhibited viral load, clearance time and symptom profiles comparable to the general population, with no severe or critical illness being found. No significant differences were noted between pregnant women over and under 35 years. BA.5 infection reduced the white blood cell counts but did not aggravate the hypercoagulability compared to the uninfected controls. Neonates of infected mothers showed a higher rate of intrauterine hypoxia than those controls. However, no SARS-CoV-2 RNA was detectable in any of the neonatal oropharyngeal swabs as well as maternal specimens, including placental membranes, amniotic fluid, vaginal secretions, breast milk, venous blood and ascites.ConclusionThis study demonstrates favorable maternal and neonatal outcomes in vaccinated pregnant women with BA.5 infection following timely medical intervention. Neonates born to infected mothers have an extremely low risk of vertical transmission. Nevertheless, enhanced prenatal care for pregnant women with COVID-19 remains essential to mitigate adverse neonatal outcomes.